Metric characteristics of new tests constructed to assess jumping agility - Nesic, G.; Stojanovic, T. (Serbian Journal of Sports Sciences, 2011)
With the aim to evaluate the metric characteristics of newly designed tests which assess jumping agility, an experimental study was conducted on a sample of 38 volleyball cadets. Six jumping agility tests were used. The sample test results had normal distribution so their sensitivity was considered satisfactory and their reliability was good (Cronbach`s alpha=0.949-0.984 and Standardized alpha=0.954-0.986). The relatively high factor loading (0.939-0.988) as well as the average inter item correlation (0.875-0.961) both indicate high homogeneity of all tests. Factor validity was also established for the tests, resulting in two latent dimensions: one yielded a projection of 4 tests (FLTJMP, FDTJMP, LATJMP, and ZIGHOP) with the coefficients ranging from 0.50 to 0.82, where the Zigzag Hop test had the highest projection and the Fast Double-Leg Touch Jump test had the lowest; the other yielded a projection of 2 tests (ASTJMP and ROTJMP) with the coefficients of 0.80 and 0.62, respectively. These results can indicate that the Astride Jump and Rotational Jump tests did not show the same factor validity as the other 4 tests so that they did not belong to the area of jumping agility but rather to another area, defined by jumping agility with additional tasks. The Fast Double-Leg Touch Jump test belonged to the primary latent dimension, but since its correlation coefficient was low, it cannot be ascertained to have measured pure jumping agility because its structure of movement leading to the jump performance also included an additional task. To summarize, the new tests showed good metric characteristics for the given study sample but due to more complex coordination required by the ASTJMP, ROTJMP, and FDTJMP tests, there should be reservations as to the measurement of pure jumping agility.